Some Approximation Properties of Series with Nonlinear Fourier Basis - Aslan, Hatice; Guven, Ali (My University, 2018)
The order of approximation of generalized de la Vallée Poussin means of series with nonlinear Fourierbasis was investigated in uniform and Hölder norms.
Keywords: Matematik